Expression of Mast Cell Density and Angiogenesis in Carcinoma in Situ and Invasive Squamous Cell Carcinoma of the Cervix (Ibrahim Cardiac Medical Journal, 2023)
Background & Objective: Studies have shown that tumor cells produce angiogenic factors that directly trigger the endothelial cells to develop. Mast cell density (MCD) and micro-vessel density (MVD) cause more aggressiveness, metastasis, poor survival rate and higher morbidity. But the exact relationship between MVD and MCD is not yet known. The present study was undertaken to find the status of MCD and MVD in carcinoma in situ (CIS) and invasive squamous cell carcinoma (ISCC) of cervix and their relationship in the context cervical carcinoma.Methods : The present cross-sectional analytical study was conducted in the Department of Pathology, Rajshahi Medical College (RMC), Rajshahi, and Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka over a period of two years between March 2017 to February 2019. Seventy blocks were taken from the cervical colposcopic biopsy materials and from the total abdominal hysterectomy specimens of patients, admitted in the Gynae and Obstetrics Department of RMCH with CIS or ISCC (diagnosed clinically and confirmed histopathologically). The sample comprised of ISCC (n = 42), CIS (n = 18) and healthy control (n = 10). The exposure variables of the study were MCD and MVD and outcome variables were CIS and ISCC.Result: In the present study, ISCC formed the main bulk (60%) of the sample followed by CIS (25.7%) and healthy control (14.3%). Nearly 80% of the cases of ISCC in our study were of Grade II and Grade III. The present study demonstrated that MVD was lowest in control subjects (8/HPF) and increases progressively from CIS (27/HPF) to Grade I (41/HPF), Grade II (45/HPF) and Grade III (51/HPF) of ISCC. The mean MVD and MCD in CIS were 27/per HPF and 33/per 10 HPF respectively. The MVD and MCD were much higher in grade I ISCC (41per/HPF and 47/per 10 HPF). But in grade II and grade III tumors, the MVD increased to 45 and 51/ per HPF respectively with the corresponding decrease in MCD to 37 and 38 per/10 HPF respectively.Conclusion: The study concluded that the MCD in ISCC is much higher compared to that in CIS. As the tumour angiogenesis progresses in ISCC with increase in the number of MVD, the MCD decreases. The MCD in cervical ISCC does not increase parallelly with the increase in MVD; rather it decreases with the advance of carcinoma from grade I to grade II & III.Ibrahim Card Med J 2021; 11 (2): 84-90